1990
DOI: 10.1002/j.1460-2075.1990.tb08262.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of an early Drosophila chorion gene promoter: expression throughout the follicular epithelium is under spatially composite regulation.

Abstract: We have fused various DNA sequences located upstream of the Drosophila melanogaster s36 chorion gene TATA box to a heterologous basal promoter and reporter gene (hsp70/lacZ). The expression of these constructs, following P‐element‐mediated germline transformation, was examined in 144 independent lines by histological staining of dissected ovaries for beta‐galactosidase activity. A short 84 bp segment of the proximal 5′ flanking DNA was sufficient to confer a wild‐type gene expression pattern, including tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
5
18
0
Order By: Relevance
“…Although our methods may miss subtle defects in main-body chorion, shark may play a DA-cell-specific role in the production/formation of chorion. Although regulatory sequences and a putative binding protein drive specific spatial expression of chorion-reporter constructs (Tolias and Kafatos, 1990;Tolias et al, 1993), no reported mutants disrupt DA-specific chorion expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although our methods may miss subtle defects in main-body chorion, shark may play a DA-cell-specific role in the production/formation of chorion. Although regulatory sequences and a putative binding protein drive specific spatial expression of chorion-reporter constructs (Tolias and Kafatos, 1990;Tolias et al, 1993), no reported mutants disrupt DA-specific chorion expression.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the first observations of overlapping expression from different enhancers date back from the 1990s (Hoch et al, 1990;Kassis, 1990;Tolias and Kafatos, 1990). In addition to these experimentally validated cases, a computational analysis has predicted the occurrence of ''shadow enhancers'' in many D. melanogaster genes that act in the segmentation cascade (Kazemian et al, 2010).…”
Section: Genes Have Multiple Enhancers With Overlapping or Very Similmentioning
confidence: 99%
“…The temporal and spatial regulation of chorion genes is reflected in morphological specializations of the eggshell along the anterior-posterior and dorsal-ventral axes (21,22) and has been documented by molecular studies at both the protein and nucleic acid levels (9,25,28,29,49,50). Detailed studies of the late-expressed siS gene suggest that its temporal control results from specific interactions between cis-regulatory DNA elements and respective positive and negative trans-acting factors, whose presence and/or activity varies during oogenesis (23).Spatial regulation is most obvious for the X-linked cluster of chorion genes and has been studied most extensively with regard to the s36 gene (28,49). Although ultimately expressed throughout the follicular epithelium (with the exception of cell populations immediately surrounding the nurse cell remnants and at the tip of the developing micropyle), this gene is initially expressed during oogenic stage 10b solely in a subpopulation of anterior dorsal follicle cells.…”
mentioning
confidence: 99%